Attention, genes, and ADHD - Levy, Florence, 1937-; Hay, David A. (New York : Psychology Press, 2021)
This book focuses on the application of behaviour genetic approaches to twin studies, and reviews diagnostic to Attention Deficit Hyperactivity Disorder (ADHD), the relationships between reading, spelling and ADHD, and family and genetic influences on speech and speech and language.
OCLC-licensed vendor bibliographic record.
Keywords: PSYCHOLOGY / Developmental / Child; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Developmental / General; Attention-deficit hyperactivity disorder; Attention-deficit hyperactivity disorder -- Genetic aspects; Attention